THEORETICAL FOUNDATIONS OF DEVELOPING MANAGEMENT COMPETENCE IN STUDENTS (SCIENCE TIME JOURNAL, 2026)
This article examines the theoretical foundations of developing management competence in students within higher education. Management competence is considered as an integrative personal and professional quality that includes knowledge, skills, values, motivation, and behavioral readiness for effective management activity. The relevance of the study is determined by the growing demand for competent specialists capable of making managerial decisions in complex and dynamic socio-economic conditions. The article systematizes key theoretical approaches, defines the structure of management competence, analyzes pedagogical conditions and methods for its development, and reviews international research and best practices.